Primary B cell Lymphoma of the tongue: a case report - Hmidi, Mounir (The African Field Epidemiology Network, 2012)
Malignant lymphoma of the oral cavity is rare and of the tongue even rarer. Location of oral lymphomas is more frequent in masticatory mucosa than in movable mucosa; the lingual and buccal mucosa is rarely involved; whereas the gingival vestibule and Waldeyer's ring seem to be the most frequent site of occurrence. We describe a 78 year old male who presented with a mass lesion primarily involving the base of tongue and was diagnosed as diffuse large B cell lymphoma. The patient was treated with CHOP chemotherapy and radiotherapy. The lesion was completely disappeared). He has currently remained disease free for 16 months. Although oral lymphoma of tongue is very uncommon, it should always be considered in differential diagnosis of various benign and malignant lesions in this region. A proper clinical evaluation, histopathologic as well as immunohistochemical evaluation of biopsy specimen may aid in the diagnosis and thus, help in proper management.